FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK REKLAME KOTA SURABAYA - Ulfiyah, Ulfiyah; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This study aimed to analyze the influence of population, number of industries and GDP towards advertisement tax revenues in the city of Surabaya. This type of research used in the study is a quantitative approach that focuses on hypothesis testing. The object of the research is the Department of Revenue and Financial Management of Surabaya in the form of tax revenues advertisement Surabaya from 2004-2014 year, and the Central Bureau of Statistics such as total population, number of industries and the GDP of the year 2004-2014. Data collection techniques using secondary data by using the method of documentation.methods of data analysis using multiple linear regression analysis. Based on the results of data analysis and hypothesis testing, it can be concluded that the variables of population, the number of industrial and regional gross domestic product a significant effect on tax revenue billboard in the city of Surabaya.Keywords: population, number of industries, GDP and advertising tax